Dynamics of Islam and Politics in the Middle East region: (Analysis of Conflicts, Roles, and Future Challenges) - Aris Munandar (An-Nur International Journal of Islamic Thought, 2024)
:  The Middle East, a region steeped in religious history, is the birthplace of major religions such as Islam, Christianity, and Judaism. Religion profoundly influences the political and social order in this region, with Islam, as the majority religion, playing a crucial role in shaping state policies and political direction. The Iranian Revolution of 1979 was a pivotal event that reinforced the influence of Islam in politics. Subsequently, Islamic movements have impacted political changes, notably during the Arab Spring, which aimed to transition autocratic systems to democracy with varied outcomes. However, the region is also marked by long-standing conflicts driven by religious, ethnic, and economic interests, exacerbated by the discovery of abundant oil resources since the 1930s. Western intervention and local political dynamics have further complicated the geopolitical landscape, resulting in prolonged conflicts with global repercussions. This research employs a quantitative approach with descriptive methods, primarily relying on a literature review. The literature review involves analyzing relevant sources such as books, journals, and articles to identify key patterns and themes, providing insight into the region's problems. Historical analysis is also utilized to understand the evolution of theories and concepts over time. The synthesized findings offer a comprehensive understanding and propose alternative solutions to the region's challenges.